POTENT IN-VITRO ANTIBACTERIAL AND ANTIFUNGAL ACTIVITIES OF PYRANO[2,3-D]PYRIMIDINE DERIVATIVES WITH QUANTITATIVE YIELD - AJMAL R. BHAT; RAJENDRA S. DONGRE; RUPALI S.SELOKAR (International Journal of Pharma and Bio Sciences, 2014)
A series of Pyrano[2,3-d]Pyrimidine derivatives were synthesis using Knoevenagel and Michael addition reaction. Investigation of antimicrobial properties were done against gram positive bacteria Staphylococcus(NCTC-7447),Bacillus cereus(ATCC-14579) and gram negative bacteria Serratia maresens(IMRU-70), Proteus merabitis (NTCC-289) using Ampicillin as standard drugs. These synthesized compounds were also screened for their antifungal activity against two species of fungi Aspergillus ochraceus Wilhelm (AUCC-230 and Penicillium chrysogenum thom (AUCC-530) using Mycostatin as standard drugs. All the tested compounds shown moderate activity. The structures of the synthesized compounds were elucidated by spectral analysis (IR, 1HNMR and 13CNMR).